(untitled) (International Journal of Food and Nutritional Sciences, 2022)
People analytics is the practise of analysing human behaviour in the workplace using data and analytical methodologies. Employee retention is one area where people analytics may be quite valuable. Organisations may acquire a better understanding of why employees leave, which individuals are at risk of leaving, and what variables contribute to high employee turnover by analysing data on employee retention. This data can assist organisations in making better educated decisions on how to boost retention and minimise turnover.